Influência do extrato de Garcinia cambogia sobre o perfil metabólico, emagrecimento e comportamento alimentar em humanos - Sant'ana, Danielle Carvalho (2019)
Obesity is a multifactorial disease of high prevalence and difficult management. It is directly related to type 2 diabetes mellitus, high blood pressure, some cancers, increased cardiovascular mortality, psychiatric disorders, making it a serious public health problem. Natural products such as Garcinia cambogia have become an alternative in treating obesity with fewer side effects. Objective: evaluate the efficacy of the herbal medicine Garcinia cambogia in causing changes in body composition, biochemical parameters, besides eating behavior in overweight and obese people. Design: clinical trial Participants: 34 female volunteers aged over 18 years old with BMI ≥ 25 Kg/m2 attended at primary health care in the municipality of Itumirim-MG, Brazil. Intervention: The volunteers included in the research were divided into 2 groups: control and treated. Both groups received a dietary plan and the treated group received 500mg of G. cambogia three times a day for a period of 4 weeks. Methodology: weight loss and body composition were assessed by anthropometry and bioimpedance data; The biochemical parameters analyzed were: total cholesterol and fractions, triglycerides, fasting glucose, urea, creatinine, creatinine clearance and transaminases; the eating behavior was assessed using the Three Factor Eating Questionnaire. All participants had their data statistically evaluated. Data were treated as medians, standard deviation and p value. Comparative analyses were performed between the medians obtained before and after the experimental intervention, within each group (control and treated) and between the two groups. Results: the treated group showed a significant difference (p<0.05), when compared to the control group in creatinine values, creatinine clearance, waist circumference, basal metabolism rate and cognitive restriction eating behavior. Other parameters evaluated, mainly body weight and body mass index, suffered significant changes resulting from experimental intervention in both control and treated groups. Some changes in biochemical parameters observed after experimental intervention were not statistically different, although they are biologically beneficial for each volunteer. Conclusion: G. cambogia extract showed an adjuvant action to the dietary plan, resulting in improvements in some morphological and biochemical parameters such as decreased abdominal circumference, increase in basal metabolism rate, decrease in creatinine value, improvement in creatinine clearance and increased cognitive restriction on eating behavior, thus representing a complementary option for overweight and obese individuals. In view of the complexity of the mechanisms involved in the genesis of obesity, the authors reaffirm that, in combination with drug and/or herbal treatment, changes in lifestyle such as healthy eating and physical activity should always be indicated.